Stanowisko Konferencji Episkopatu Polski wobec wyborów parlamentarnych w 1991 roku (Politeja, 2018)
The Position of the Polish Episcopal Conference on the Parliamentary Elections in 1991The purpose of this article is to show the position of the Conference of the Polish Episcopate on the parliamentary elections in 1991. In official pronouncements of the Conference of the Polish Episcopate on this issue, as well as in the statements of individual bishops you can find two common elements. Firstly, noticeable is the identification of the category of the Polish nation, Catholics and society. Hence the belief that the institutions of a democratic state should uphold Christian values and national. Secondly, the Conference of the Polish Episcopate harbored the misconception by unanimity Catholics in Poland in terms of political views. It quickly turned out that the majority of the population does not recognize the role of the Church as the subject of political life. Already in the early nineties, and especially after the parliamentary elections in 1991, there have been numerous discussions on clericalism and anti‑clericalism.